Synthesis of Zigzag Carbon Nanobelts through Scholl Reactions. Issue 18 (17th March 2021) - Xia, Zeming; Pun, Sai Ho; Chen, Han; Miao, Qian
Abstract: Zigzag carbon nanobelts are a long‐sought‐after target for organic synthesis. Herein we report new strategies for designing and synthesizing unprecedented zigzag carbon nanobelts, which present a wave‐like arrangement of hexagons in the unrolled lattice of ( n, 0) single wall carbon nanotubes ( n =16 or 24). The precursors of these zigzag carbon nanobelts are hybrid cyclic arylene oligomers consisting of meta ‐phenylene and 2, 6‐naphthalenylene as well as para ‐phenylene units. The Scholl reactions of these cyclic arylene oligomers form multiple carbon‐carbon bonds selectively at the α‐positions of naphthalene units resulting in the corresponding zigzag carbon nanobelts. As monitored with fluorescence spectroscopy, one of these nanobelts binds C60 with an association constant as high as (6.6±1.1)×10 6 M −1 in the solution in toluene. Computational studies combining linear regression analysis and hypothetical homodesmotic reactions reveal that these zigzag nanobelts have strain in the range of 67.5 to 69.6 kcal mol −1, and the ladderization step through Scholl reactions is accompanied by increase of strain as large as 69.6 kcal mol −1 . The successful synthesis of these nanobelts demonstrates the powerfulness and efficiency of Scholl reactions in synthesizing strained polycyclic aromatics. Abstract : Regioselective Scholl reactions have enabled successful synthesis of unprecedented zigzag carbon nanobelts, which present a wave‐like arrangement of hexagons in the unrolled lattice of ( n, 0) single wall carbon nanotubes ( n =16 or 24). As monitored with fluorescence spectroscopy, one of these nanobelts binds C60 with an association constant as high as (6.6±1.1)×10 6 M −1 in toluene.